2013
DOI: 10.1183/09031936.00039513
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lung function and health status in adult survivors of bronchopulmonary dysplasia

Abstract: More infants with bronchopulmonary dysplasia (BPD) now survive to adulthood, but little is known regarding persisting respiratory impairment. We report respiratory symptoms, lung function and health-related quality of life (HRQoL) in adult BPD survivors compared with preterm (non-BPD) and fullterm controls.Respiratory symptoms (European Community Respiratory Health Survey) and HRQoL (EuroQol (EQ)-5D) were measured in 72 adult BPD survivors (mean¡SD study age 24.1¡4.0 years; mean¡SD gestational age 27.1¡2.1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 31 publications
6
129
2
1
Order By: Relevance
“…2,34 Another large study was published from Belfast, Northern Ireland, with 96 small preterm survivors (56 with BPD) and 55 control subjects. 12 Consistent with our findings and those previously reported in children, 4 these studies showed reduced airflow also in VLBW adults without BPD, although this outcome was strongest in the BPD-VLBW groups. Our results extend these findings by demonstrating that the effects of VLBW birth per se and BPD seem to override the effects of most other clinical conditions, including intrauterine growth restriction, growth restriction during postnatal care, and neonatal RDS, which had very little additional value in predicting lung function in young adult life.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…2,34 Another large study was published from Belfast, Northern Ireland, with 96 small preterm survivors (56 with BPD) and 55 control subjects. 12 Consistent with our findings and those previously reported in children, 4 these studies showed reduced airflow also in VLBW adults without BPD, although this outcome was strongest in the BPD-VLBW groups. Our results extend these findings by demonstrating that the effects of VLBW birth per se and BPD seem to override the effects of most other clinical conditions, including intrauterine growth restriction, growth restriction during postnatal care, and neonatal RDS, which had very little additional value in predicting lung function in young adult life.…”
Section: Discussionsupporting
confidence: 83%
“…5 Much of the existing evidence focuses on adults with a history of BPD, who do have more pulmonary symptoms and respiratory function abnormalities (including obstructed airflow) than those born at term. 2,[6][7][8][9][10][11][12] Whether this outcome applies to adults born preterm at VLBW who have no history of BPD is less conclusive. Most studies may not include a sufficient number of subjects to distinguish between those with a history of BPD and those without.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[38][39][40] There is however, still a lack of knowledge about the prevalence and magnitude of chronic respiratory morbidity after extremely preterm birth. We find it deeply concerning that asthma-like disease was very prevalent among children born extremely preterm and that up to half of the children born at 22-24 weeks of gestation exhibited a lung function below the lower limits of normal.…”
Section: Clinical Aspects Of the Resultsmentioning
confidence: 99%
“…It may be the longest-lasting obstructive lung disease in humans, often unrecognized and untreated in BPD survivors. 5,[7][8][9] More than half of 11-year-olds with a history of BPD had chronic cough and asthma-like symptoms than their term-born peers, but fewer than half were treated. 8 Adults who had BPD as infants are at increased risk for subclinical right ventricular dysfunction, obstructive lung disease, exercise intolerance, emphysema, asthma-like symptoms, and reduced quality of life due to respiratory symptoms.…”
mentioning
confidence: 99%
“…6 One study found that these adults were twice as likely to report wheezing and three times more likely to use asthma medications than controls. 9 Is an elevated ETCO 2 on a neonatal PSG a biomarker for neurodevelopmental outcome? Permissive hypercapnia (intentionally reducing tidal volumes to increase ETCO 2 levels and mild hypercapnia during the first 2 weeks following birth) is one of the treatment strategies that neonatologists have been using to decrease risk for ventilator-induced lung injury and BPD.…”
mentioning
confidence: 99%